The effectiveness of oil spill dispersant addition for phytoremediation of petroleum-contaminated soil using Ricinus communis L - Sari Yulia Hasibuan; Mohamad Yani; Irdika Mansur (Journal of Degraded and Mining Lands Management, 2019)
Phytoremediation is one of the most effective and environmental-friendly methods in retrieving oil-contaminated soil. The decline of Total Petroleum Hydrocarbon (TPH) oil in the phytoremediation process will be accelerated by Oil Spill Dispersant (OSD) as a surfactant and the use of Ricinus communis L. plant. Commercial OSD products used in the remediation process are S200 OSD which contains LAS surfactant, which is a US EPA recommendation and is known to be less environmental-friendly, so SBRC-IPB develops OSD containing palm oil surfactants and is environmental-friendly. The purpose of this study was to determine the performance of OSD and R. communis to reduce TPH. This study used a completely randomized design with two factors, namely OSD and plant use. The results of this study indicated that OSD from SBRC-IPB improved plant growth, increased dry plant biomass, accelerated the decrease in TPH and increased the bacterial population compared to the S200 OSD and control. The combination of OSD from SBRC and R. communis was able to degrade TPH better than S200 OSD, with and without R. communis, with TPH concentrations of 30,000 ppm (3%) to 2,333 ppm (0.2%) for 20 weeks. This showed that the use of OSD was able to provide a positive response in the phytoremediation process of land contaminated with petroleum